2022
DOI: 10.3390/ijms23158602
|View full text |Cite
|
Sign up to set email alerts
|

p-Coumaric acid, Kaempferol, Astragalin and Tiliroside Influence the Expression of Glycoforms in AGS Gastric Cancer Cells

Abstract: Abnormal glycosylation of cancer cells is considered a key factor of carcinogenesis related to growth, proliferation, migration and invasion of tumor cells. Many plant-based polyphenolic compounds reveal potential anti-cancer properties effecting cellular signaling systems. Herein, we assessed the effects of phenolic acid, p-coumaric acid and flavonoids such as kaempferol, astragalin or tiliroside on expression of selected cancer-related glycoforms and enzymes involved in their formation in AGS gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Scutellarin suppressed GC by altering lactate dehydrogenase profile, DNA Frontiers in Pharmacology frontiersin.org density, mucus content and acidity (Sun and Meng, 2022). Kaempferol, p-Coumaric acid, Astragalin and Tiliroside influence abnormal glycosylation of GC cells, so as to exert the anticancer effect (Radziejewska et al, 2022). DIM suppressed GC via mediated ferroptosis, store-operated calcium entry, gastric cancerderived mesenchymal stem cells, endogenous hydrogen sulfide biosynthesis (Ye et al, 2020;Ye et al, 2021b;Shi et al, 2021;Ye et al, 2022).…”
Section: Other Possible Mechanismsmentioning
confidence: 99%
“…Scutellarin suppressed GC by altering lactate dehydrogenase profile, DNA Frontiers in Pharmacology frontiersin.org density, mucus content and acidity (Sun and Meng, 2022). Kaempferol, p-Coumaric acid, Astragalin and Tiliroside influence abnormal glycosylation of GC cells, so as to exert the anticancer effect (Radziejewska et al, 2022). DIM suppressed GC via mediated ferroptosis, store-operated calcium entry, gastric cancerderived mesenchymal stem cells, endogenous hydrogen sulfide biosynthesis (Ye et al, 2020;Ye et al, 2021b;Shi et al, 2021;Ye et al, 2022).…”
Section: Other Possible Mechanismsmentioning
confidence: 99%
“…It can inhibit the cell cycle of GC cells, promote autophagy of GC cells. It has therapeutic potential for anti-GC effects [ 28 , 29 ]. In conclusion, the above studies confirm that XSLJZT, as a compound of traditional Chinese medicine, contains major active ingredients that have significant inhibitory effects on GC.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Radziejewska et al observed that AG blocked the synthesis of Tn antigen, sialyl Tn antigen, and T antigen via suppressing the expressions of the glycosyltransferases ppGalNAcT2, ST6GalNAcT2, C1GalT1, St3Gal-IV, and FUT4 in AGS cells. Moreover, AG also decreased the level of NF-κB, which suggests that the NF-κB signaling pathway might be involved in the inhibition of the glycosylation process ( Radziejewska et al, 2022 ). In addition, AG was reported to induce the death of gastric cancer cells and reduce cancer cell viability in a gastric cancer cell-based xenograft mouse without obvious toxicity.…”
Section: Pharmacological Effects Of Agmentioning
confidence: 99%